Young Singaporean women's knowledge of cervical cancer and pap smear screening: a descriptive study. Issue 23 (December 2013) - Shea, Juanna; Klainin‐Yobas, Piyanee; Mackey, Sandra
Abstract : Aims and objectives: To assess the knowledge of young female Singaporeans regarding cervical cancer and pap smear, the intention to participate in pap smear and whether there is any relationship between knowledge and intention to participate in pap smear screening. Background: While cervical cancer has poor prognosis in the later stages, pap smear is effective in identifying precancerous lesions, which are more treatable. Pap smear screening is available to women in Singapore, but its uptake is opportunistic. Research has shown that knowledge about pap smear and cervical cancer is important determinant of screening behaviour in Singaporean women. Design: Cross‐sectional descriptive correlational design was used. Methods: Three hundred and ninety‐three young Singaporean undergraduates, aged 18–25 years, were recruited via convenience sampling from a local university over a four‐month period. Data were collected through self‐administered questionnaires. Results: Majority of the participants knew the term 'pap smear' and its function. However, knowledge of the risk factors for cervical cancer was lacking among the young women. Knowledge of pap smear and cervical cancer had a weak correlation with the intention to go for the future uptake of pap smear. Conclusions: Educational efforts among younger Singaporean women on the knowledge of pap smear and risk factors for cervical cancer are needed. Improving knowledge will enable them to understand the importance of reducing exposure to risk factors and regular pap smear screening. Relevance to clinical practice: All health professionals working with young Asian women should be prepared to educate and counsel young women to participate in pap smear screening according to current guidelines. In particular, knowledge of the age to attend the first pap smear and the recommended frequency for screening need to be targeted for health education.